2022
DOI: 10.3390/educsci12090598
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning in Biomedical Engineering Education Using Wearable Devices: A Case Study in a Biomedical Signals and Systems Analysis Course

Abstract: Biomedical engineering (BME) is one of the fastest-growing engineering fields worldwide. BME professionals are extensively employed in the health technology and healthcare industries. Hence, their education must prepare them to face the challenge of a rapidly evolving technological environment. Biomedical signals and systems analysis is essential to BME undergraduate education. Unfortunately, students often underestimate the importance of their courses as they do not perceive these courses’ practical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This highlights the challenges of BME and raises questions about how to design curricula for producing engineering graduates who are “well‐rounded and capable of dealing with complex problems” (Ertas et al., 2003, p. 292). This may justify the recent and strong focus on transdisciplinarity (Ertas et al., 2003; Montesinos et al., 2023) to develop the desired depth and breadth associated with a comprehensive understanding of societal needs.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the challenges of BME and raises questions about how to design curricula for producing engineering graduates who are “well‐rounded and capable of dealing with complex problems” (Ertas et al., 2003, p. 292). This may justify the recent and strong focus on transdisciplinarity (Ertas et al., 2003; Montesinos et al., 2023) to develop the desired depth and breadth associated with a comprehensive understanding of societal needs.…”
Section: Discussionmentioning
confidence: 99%
“…First, the proposed learning experiences must be adapted to new curricular developments (e.g., updates to the biomedical engineering curriculum) using state-of-the-art instructional methods, such as service and challenge-based learning, or problem-solving methodologies, such as design thinking. In addition, new learning experiences can be created in the wider variety of learning spaces supported by state-of-the-art technologies, fostering a ubiquitous learning [ 22 ]. Furthermore, the assessment of students’ learning could be improved by incorporating a tool for students to track and reflect on their learning process, such as a regular learning journal, to foster mandatory reflection.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms include computer simulation, laboratory experiments, design courses, guest speakers, industry-sponsored design projects, field trips to hospitals and medical device companies, and internships. Furthermore, some instructional methods have been proposed to improve biomedical engineering education, including problem-based, project-based, challenge-based, and experiential learning, particularly in North American higher education institutions [ 16 – 22 ]. These methods engage students in collaboratively developing solutions to real-world problems based on crucial concepts in the discipline, thus fostering disciplinary knowledge and creative thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Medical and engineering students alike have voiced an interest in transdisciplinary collaboration but current practices often fall short of expectations 6 . Furthermore, similar pedagogical approaches have demonstrated that transdisciplinary instruction is a useful means for Biomedical Engineering students to design solutions for complex problems in health care systems 10 . In this way, the course curriculum aims to address not only the need of students but also best educational practices.…”
Section: Discussionmentioning
confidence: 99%